Pengaruh Tingkat Keseriusan Kecurangan, Personal Cost, dan Komitmen Organisasi Terhadap Kecenderungan Melakukan Whistleblowing - Nur Fauziah Busra; Muhammad Ahyaruddin; Agustiawan Agustiawan (Muhammadiyah Riau Accounting and Business Journal, 2019)
This study aims to investigate the factors that influence an individual's tendency to whistleblowing. Specifically, this study focused on the effect of severity of fraud, personal cost and organizational commitment on tendency to whistleblowing. The samples of this study were civil servants of Regional Development Planning Agency (BAPPEDA) Pekanbaru city. This study uses questionnaire to collect the data and uses multiple regression to test the hypothesis. The results of study showed that severity of fraud and organizational commitment have significantly effect on tendency to whistleblowing. But, this study did not find any significant effect among personal cost and tendency to whistleblowing. This means that the civil servants do not consider personal cost as a factor that will influence their intention to take or not take whistleblowing.